Optimasi Hasil Produksi Keranjang Rotan Menggunakan Metode Karush-Kuhn-Tucker (Studi Kasus Rumahan Keranjang Rotan di Desa Buluh Rampai - Belasandi, Belasandi; Arnelis, Arnelis (Journal of Mathematics UNP, 2023)
Optimization aims to obtain extreme values, either maximizing or minimizing a certain function with its limiting factors. This research was conducted in the rattan basket home industry of Buluh Rampai village by taking secondary data. To find out production results and maximum profits based on the availability of raw materials, time, labor and production capital, we use the Karush-Kuhn-Tucker method. This method can determine the optimum value of a constraint function without looking at its linear or nonlinear properties. This method is a development of the Lagrange method with matrix multiplication using the Matlab application. Based on the results of research using the Karush-Kuhn-Tucker method, it was found that the number of weighing rattan baskets produced was 116, 225 small round rattan baskets, 360 large round rattan baskets, and 77 ambungs with a maximum profit of IDR 41,985,313.